Penerapan Strategi Pembelajaran Reciprocal Learning untuk Meningkatkan Hasil Belajar Siswa di SMA Negeri 1 Pancur Batu: (Application Of Reciprocal Learning Strategy to Increase Student Learning Outcomes In Sma Negeri 1 Pancur Batu) - Halimatussya’diyah Halimatussya’diyah; Jeneri Puspita Sari; Sauda Julia Intanna; Siti Nurbaya; Indayana Febriani Tanjung (BIODIK, 2023)
This research is a classroom action research conducted in two cycles. Each cycle consists of planning, implementation, observation and observation. The subjects of this study were students of class X MIA SMA Negeri 1 Pancur Batu Academic year 2021 / 2022. This study aims to determine the improvement in learning outcomes of class X MIA students in Biology subjects through learning strategies (Reciprocal Learning). The instruments used are observation, pretest and posttest. Student observation sheet The indicator of the success of this study is seen from the mastery of student learning who achieves the Minimum Completeness Criteria (KKM) of 80. From the results of the study, in the first cycle the student learning completeness achieved is 75%, and the second cycle is 85%, where the increase the percentage of student learning outcomes from cycle I to cycle II reached 10%. Based on the results of this study, it can be concluded that student learning outcomes in Biology can be increased through Reciprocal Learning learning strategies, and have the advantage of developing student knowledge, forming collaboration between students and creating student curiosity, especially in the environment around the school at SMA Negeri 1 Pancur Batu. Key words: Classroom Action Research, student learning outcomes, Reciprocal Learning Model   ABSTRAK Eksplorasi ini merupakan penelitian kegiatan hasil studi yang diarahkan dalam dua siklus. Setiap siklus terdiri dari penyusunan, pelaksanaan, persepsi dan persepsi. Subyek review ini adalah siswa kelas X MIA SMA Negeri 1 Pancur Batu tahun ajaran 2021/2022. Review ini berencana untuk memutuskan peningkatan hasil belajar siswa kelas X MIA pada mata pelajaran Biologi melalui teknik pembelajaran (Reciprocal Learning). Instrumen yang digunakan adalah persepsi, pretest dan postest. Lembar persepsi siswa kemajuan penelitian ini dilihat dari kewenangan pencapaian siswa yang mencapai Kriteria Ketuntasan Minimal (KKM) 80. Dari hasil review, pada siklus utama pemenuhan pembelajaran siswa yang dicapai adalah 75%. , dan siklus II sebesar 85%, dimana laju pemuaian pada siswa yang memperoleh hasil dari siklus I ke siklus II mencapai 10%.  Kata kunci: Penelitian Tindakan Kelas, hasil belajar siswa, Model Pembelajaran Reciprocal